PENGARUH KOMPETENSI, BEBAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA CV. TRI TUNGGAL SEJAHTERA - Intan Marleni; I Wayan Sujana; Ni Nyoman Ari Novarini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Human resources are the most important factor in every company activity because however sophisticated the technology used without being supported by humans as the executor of operational activities will not be able to produce output that is in accordance with the expected level of efficiency. The role of human resources in organizations actually existed when the organization was recognized as a forum for joint efforts to achieve a goal. The sample in this study were all active employees of CV. Tri Tunggal Sejahtera as many as 38 people. The sampling technique used is the saturated sampling method. Data collection techniques used in this study were observation, interviews and questionnaires. Data analysis techniques include validity test, reliability test, classical assumption test, linear regression analysis multiple, correlation analysis, determination analysis (R2), f test and t test. The results of the study indicate that competence, workload and work discipline have a positive and significant effect on employee performance, so the leadership should be able to provide training to each employee, balance the workload with commensurate results and build good communication with employees, for example starting from the leader himself so that can improve employee performance on CV. Prosperous Tri Tunggal.